Empowering a Methanol-Dependent Escherichia coli via Adaptive Evolution Using a High-Throughput Microbial Microdroplet Culture System - Wang, Jia; Jian, Xingjin; Xing, Xin-Hui; Zhang, Chong; Fei, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Recently, a methanol-essential Escherichia coli was constructed, whereas this strain is highly dependent on the supply of gluconate as a cosubstrate for growth. Adaptive laboratory evolution is commonly applied to obtain mutants with specific phenotypes under certain selected pressure. However, conventional adaptive evolution approaches not only result in labor and time-consuming but also come with lower throughput and inefficiency. In order to empower the aforementioned E. coli with reduced gluconate usage and enhanced growth rate, an irrational strategy based on a microbial microdroplet culture (MMC) platform was developed in this study. Given the automatic high-throughput selction of the MMC, a three-stage regime of an adaptive evolution via gradually decreasing the availability of gluconate during the cultivation was performed for 50 days continuously in order to obtain the mutaions. Finally, a candidate mutant was obtained with a 3X faster growth rate, 43% shorter lag phase, and 40% less gluconate usage. Moreover, the gene mutations of gntU, idnT, edd and pckA were identified by analyzing the whole-genome sequencing of mutants, which are strongly associated with the efficienty of gluconate uptake and cell growth. In conclusion, we have successfully demonstrated the feasibility of using MMC platform to empower the target strain with specific requirements in a manner of labor, time efficiency, and directed evolution.